Audiomarketing - music as a tool for indirect persuasion - Makomaska, Sylwia (Interdisciplinary Studies in Musicology, 2018)
In modern society, music penetrates most of our everyday activities, and so one is not surprised that it has become commonplace, and even expected by consumers, in places of sale. Contemporary shops are no longer merely points of sale. They have become a sort of medium between clients, on one hand, and vendors and producers, on the other. Audiomarketing is a term used to define a modern marketing tool that uses music to create the unique atmosphere of a particular place and to influence consumer in places of sale. To explain the audiomarketing phenomenon, a review of selected studies concerning the problem of emotional responses to music has been presented. These findings are supported by a review of some investigations indicating that music can have a strong impact on consumer behaviour (e.g. music and the speed of customer activity, music and time perception, the effects of music on sales, etc.). The presented examples of experimental research provide excellent proof that it is worth introducing suitably chosen music into a space where people buy and consume. This is due above all to the fact that present-day society, overwhelmed by vociferous messages, prefers emotional arguments, and music can act as an excellent tool for communicating with consumers on an emotional level.